Humor, Neuroscience, and Mathematics Education: A Systematized Literature Review - Quintuña Padilla, Sandro Xavier; Herrera Caldas, Verónica Alexandra (Revista Ecos de la Academia, 2025)
Humor has been present in classrooms across different educational settings, and although sometimes underestimated by educators, it was empirically known to create positive emotional moments. Recent research allows us to value this aspect and validate that it plays an important role in learning. When applied to complex subjects like mathematics, it could become a pedagogical tool for reducing anxiety and improving learning. Along with advances in humor research in education, neuroscience has provided concepts and principles that help us understand the cognitive and emotional processes that accompany the use of humor in education. This systematized literature review examines this triple intersection: humor, neuroscience, and mathematics teaching. Following a selection process, 27 articles published between 2007 and 2024 were identified. The analysis performed led to a conceptual framework where convergence occurs at the affective, cognitive, and pedagogical levels. Several significant findings emerge from this review, particularly the activation of overlapping brain regions during both mathematical problem-solving and humor processing, along with shared mechanisms of cognitive flexibility and divergent thinking. The conclusion is that humor can be systematically integrated into education, supported by neuroscientific evidence and principles, to enhance the mathematics learning experience.